Pan-immune-inflammation value is associated with the clinical stage of colorectal cancer - Zhao, HanZheng; Chen, Xingyu; Zhang, WenHui; Cheng, Die; Lu, Yanjie; Wang, Cheng; Li, JunHu; You, LiuPing; Yu, JiaYong; Guo, WenLong; Li, YuHong; Huang, YueNan (Frontiers in Surgery, 2022)
Objective: We investigated the clinical significance of preoperative pan-immune-inflammation value (PIV) in patients with colorectal cancer (CRC). Methods: In this retrospective study, 366 cases who underwent surgery for CRC were enrolled. Their clinical data were collected. PIV was calculated with the formula PIV = [neutrophil count (109/L) x platelet count (109/L) x monocyte count (109/L) /lymphocyte count (109/L). Patients were divided into high PIV (> median PIV) and low PIV (< median PIV) groups. The relationship between PIV and clinicopathological features of CRC was investigated. Receiver operating characteristic (ROC) curve was plotted to indicate the value of immune-inflammatory biomarkers (IIBs) in predicting the TNM stage of CRC, and the area under the curve (AUC) was calculated to evaluate the actual clinical value of IIBs. AUC > 0.5 and closer to 1 indicated the better predictive efficacy. The influencing factors of PIV in CRC were analyzed. Results: We found that PIV was positively correlated with tumor size (r = 0.300, P <0.05), carcinoembryonic antigen (CEA) (r = 0.214, P <0.05) and carbohydrate antigen 125 (CA-125) (r = 0.249, P <0.05), but negatively correlated with albumin (Alb) (r= -0.242, P<0.05). PIV was significantly different in patients with different tumor locations (left or right), surgical methods (laparotomy versus laparoscopic surgery) (P <0.05)，and patients with different pathological T stages, N-stage and TNM stages (P <0.05). ROC curve analysis of IIBs showed the AUC of PIV was greater than other markers when combined with CEA or carbohydrate antigen 19-9 (CA19-9). Multivariate regression analysis identified T stage, CEA, Alb, and tumor size as the independent influential factors of PIV in CRC. Conclusion: PIV is associated with the tumor stage in patients with CRC, which may be useful in preoperative assessment of CRC.